The Use Of Chairil Anwar's " Aku" Poem In History Learning - Pratiwi, Adita (JURNAL HISTORICA, 2024)
Poetry is a type of literary work. Poetry is the result of the expression of the poet's feelings with language that is bound by rhyme, line, rhythm, and stanzas and contains meaning. One of Chairil Anwar's famous poems entitled "I" is a poem that was born during the period of the national movement. The poem "I am" poetry with the theme of the spirit of struggle, is only present as an encouragement for the fighters who are fighting for Indonesian independence. The method used in this paper is literature study, which aims to look at the meaning and history of the poem "Aku" as a medium for learning history. The poem "Aku" can be a medium for learning history, especially in terms of shaping the character of students, becoming someone who has nationalism and a high fighting spirit to defend Indonesia's independence.